A PRODUÇÃO DO CONHECIMENTO SOBRE PIBID EDUCAÇÃO FÍSICA NA PÓS-GRADUAÇÃO STRICTO SENSU EM EDUCAÇÃO E EDUCAÇÃO FÍSICA - Halisson Keliton Ramos dos Santos (Muiraquitã, 2020)
This article is part of the master’s study that investigated the production strictly on the Institutional Program for Teaching Initiation Scholarships (Pibid). Pibid is certainly one of the most well-known programs in the area of teacher training at the Ministry of Education. Thus, the objective of this text is to present how the pro-duction of stricto-sense knowledge is characterized in Physical Education and Education that took Pibid Physical Education as an object of study at national level between 2009 and 2016. A bibliographical-documentary research was carried out. The analysis was concerned with theoretical-methodological aspects, the conclusions and recom-mendations of the works on Pibid. The results show that of the theories used, the pedagogies of learning to learn ac-count for 71.4% of the total publications. This reinforces a characteristic of the productions on educational policies.